2023
DOI: 10.3389/fnut.2022.1075744
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to adherence in time-restricted eating clinical trials: An early preliminary review

Abstract: Time-restricted eating (TRE) has shown potential benefits in optimizing the body's circadian rhythms and improving cardiometabolic health. However, as with all dietary interventions, a participant's ability to adhere to the protocol may be largely influenced by a variety of lifestyle factors. In TRE trials that reported participants' rates of adherence, the percentage of total days with successful adherence to TRE ranged from 47% to 95%. The purpose of this review is to (1) summarize findings of lifestyle fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This corresponds approximately to the adherence seen in other studies with comparable intervention. 24 Only 3 patients decided to voluntarily cross over to the regular diet group after 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds approximately to the adherence seen in other studies with comparable intervention. 24 Only 3 patients decided to voluntarily cross over to the regular diet group after 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that TRE adherence rates ranged from 47% to 95%. 181 To get around this, future trials might need to tailor their protocol to potentials barriers such as social life, work schedule, cultural and religious influences. Moreover, it is desirable to choose eating intervals of 6-10 h so that participants can eat within a reasonable time frame.…”
Section: Potential Applications and Common Concerns Of Trementioning
confidence: 99%
“…Furthermore, adherence to TRE is one of the biggest long‐term concerns. Previous studies showed that TRE adherence rates ranged from 47% to 95% 181 . To get around this, future trials might need to tailor their protocol to potentials barriers such as social life, work schedule, cultural and religious influences.…”
Section: Potential Applications and Common Concerns Of Trementioning
confidence: 99%